Ljubljančanka Ivana Kobilca - Šorn, Mojca (Prispevki za novejšo zgodovino, 2022)
Based on previous scientific findings, expert contributions, and newspaper sources, the following article introduces Ivana Kobilca and places her in the broader context of the time and place in which she lived and worked. Although her calling summoned her to many great European cities for several decades, the painter always maintained ties with her family and her birthplace, Ljubljana. The author of the article at hand presents these with the help of archival materials, particularly Kobilca’s correspondence, which is a part of the Pintar family legacy and is kept at the National Gallery.
Keywords: feminizem; Jugoslavija; Kobilca, Ivana; Ljubljana; položaj žensk; Slovenske slikarke; Sodobno slikarstvo; spomini